Improvement of Science Learning Outcomes With Interactive Powerpoint Media Class V Students Of SDN 01 Ambowetan - Anggraeni, Yuli (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the science learning outcomes of animal classification materials based on the type of food for grade V SDN 01 Ambowetan students through the use of powerpoint media. The subjects in this study were students of class V SDN 01 Ambowetan consisting of 20 boys and 25 girls. Classroom Action Research Methods implemented in 3 cycles. The research design starts from the planning stage, action implementation, observation, and reflection. In learning activities, the use of powerpoint learning media and learning outcomes has increased in each cycle. In cycle I (70%), cycle II (90%) and cycle III (100%). Completeness of learning in cycle I (71.11%), cycle II and cycle III (100%) while the class average in cycle I (73.69), cycle II (82.49), and cycle III (86.67) ). The conclusion that can be drawn is that learning with the use of powerpoint media can improve science learning outcomes. The subject of Animal Classification by Type of Food in grade V SDN 01 Ambowetan students